Homework Involvement and Academic Achievement of Native and Immigrant Students - Suárez, Natalia; Regueiro, Bibiana; Epstein, Joyce L.; Piñeiro, Isabel; Díaz, Sara M.; Valle, Antonio (Frontiers in Psychology, 2016)
Homework is a debated issue in society and its relationship with academic achievement has been deeply studied in the last years. Nowadays, schools are multicultural stages in which students from different cultures and ethnicities work together. In this sense, the present study aims to compare homework involvement and academic achievement in a sample of native and immigrant students, as well as to study immigrant students’ relationship between homework involvement and Math achievement. The sample included 1328 students, 10 to 16 years old from Spanish families (85.6%) or are immigrant students or students of immigrant origin (14.4%) from South America, Europe, Africa, and Asia. The study was developed considering three informants: elementary and secondary students, their parents and their teachers. Results showed higher involvement in homework in native students than in immigrant. Between immigrants students, those who are more involved in homework have better academic achievement in Math at secondary grades. There weren’t found gender differences on homework involvement but age differences were reported. Immigrant students are less involved in homework at secondary grades that students in elementary grades. The study highlights the relevance of homework involvement in academic achievement in immigrant students.